HIV taken by STORM: Super-resolution fluorescence microscopy of a viral infection - Pereira Cândida F; Rossy Jérémie; Owen Dylan M; Mak Johnson; Gaus Katharina (Virology Journal, 2012)
Abstract Background The visualization of viral proteins has been hindered by the resolution limit of conventional fluorescent microscopes, as the dimension of any single fluorescent signal is often greater than most virion particles. Super-resolution microscopy has the potential to unveil the distribution of proteins at the resolution approaching electron microscopy without relying on morphological features of existing characteristics of the biological specimen that are needed in EM. Results Using direct stochastic optical reconstruction microscopy (dSTORM) to achieve a lateral resolution of 15–20 nm, we quantified the 2-D molecular distribution of the major structural proteins of the infectious human immunodeficiency virus type 1 (HIV-1) before and after infection of lymphoid cells. We determined that the HIV-1 matrix and capsid proteins undergo restructuring soon after HIV-1 infection. Conclusions This study provides the proof-of-concept for the use of dSTORM to visualize the changes in the molecular distribution of viral proteins during an infection.